2013
DOI: 10.1186/1471-2474-14-228
|View full text |Cite
|
Sign up to set email alerts
|

Low dose native type II collagen prevents pain in a rat osteoarthritis model

Abstract: BackgroundOsteoarthritis is the most widespread joint-affecting disease. Patients with osteoarthritis experience pain and impaired mobility resulting in marked reduction of quality of life. A progressive cartilage loss is responsible of an evolving disease difficult to treat. The characteristic of chronicity determines the need of new active disease modifying drugs. Aim of the present research is to evaluate the role of low doses of native type II collagen in the rat model of osteoarthritis induced by sodium m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 47 publications
1
58
0
5
Order By: Relevance
“…In animal studies, pain can be evaluated indirectly, using for instance weight bearing or gait analyses, or directly by assessing for instance paw withdrawal threshold in response to mechanical or thermal stimuli . We only tested one of these parameters, but it has been reported that a pain‐relieving substance has similar effects on multiple pain‐related outcome measures in a rat MIA OA model . Our findings show a decrease in pain, as measured by a significant increased weight bearing of the affected limb after intra‐articular application of MSCs.…”
Section: Discussionmentioning
confidence: 84%
“…In animal studies, pain can be evaluated indirectly, using for instance weight bearing or gait analyses, or directly by assessing for instance paw withdrawal threshold in response to mechanical or thermal stimuli . We only tested one of these parameters, but it has been reported that a pain‐relieving substance has similar effects on multiple pain‐related outcome measures in a rat MIA OA model . Our findings show a decrease in pain, as measured by a significant increased weight bearing of the affected limb after intra‐articular application of MSCs.…”
Section: Discussionmentioning
confidence: 84%
“…The rats ( n  = 6) receiving only the saline solution served as sham control animals (group I) throughout the experiment. The pain sensitivity of the knee joints was measured before MIA injection and once every week after MIA injection as described by Di Cesare et al [21]. The Pressure Application Measurement device (PAM; Ugo Basile, Italy) was used to measure the mechanical pain threshold of the knee joints.…”
Section: Methodsmentioning
confidence: 99%
“…The first inflammatory phase (day 7 after MIA injection) is followed by an increasing neuropathic component leading to enhanced responses to normal or suprathreshold stimulation (allodynia-and hyperalgesia-related measurements; Di Cesare Mannelli et al, 2013b). On day 14, Capparis spinosa preparations relieved MIAdependent articular pain (both hypersensitivity and spontaneous pain) showing efficacy also against a predominantly neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%